Phylogenetic inference and macro-evolutionary patterns in Ficinia Schrad. (Cyperaceae) - Francis, Caitlynne Melanie (Department of Biological Sciences, 2017)
The genus Ficinia Schrad. has its centre of diversity in the Cape Floristic Region and phylogenetic relationships within this genus have not been fully studied representing a gap in the body of work on the Cyperaceae. Phylogenetic analyses provide strong support for the sister relationship between Isolepis and Ficinia in both parsimony and Bayesian analyses (BP = 96; PP = 1). Isolepis marginata consistently resolved as more closely related to the Ficinia clade than to the rest of the species in Isolepis. Ficinia undosa was positioned outside its own genus (as well as the entire FiciniaIsolepis clade) rendering the genus paraphyletic. This species appears to be more closely related to members of the Scirpus falsus-Scoipoides clade. As in previous studies, the New Zealand monotypic genus Desmoschoenus is resolved as a member of Ficinia and is closely allied with Ficinia pallens (BP=43, PP=0.56). Macroevolutionary reconstruction of characters such as life form and the presence of a gynophore disk revealed interesting patterns within the genus as well. Perennial habit is a synapomorphy for Ficinia and distinguishes it from the generally annual sistergenus Isolepis. Though a young genus when compared with Isolepis, Ficinia has radiated in the CFR quite rapidly following the -shift toward Mediterranean climate in this region. While support across the tree is quite low, due perhaps to the slow mutation rate among recent and rapidly radiated perennials, several relationships within m the genus are resolved with moderate nodal support.